Assessment of knowledge, attitudes and practices toward prevention of hepatitis B virus infection among medical students in Geetanjali Medical College, Udaipur - Sharma, Sachin; Dixit, Mukul; Mittal, Hemlata; Jain, Jyoti; Jain, Divya; Khandelwal, Anmol (International Journal Of Community Medicine And Public Health, 2018)
Background: Hepatitis B virus (HBV) infection is one of the major public health problems in the world. According to the recent estimates, about one-third of the world population is infected with HBV. Health care workers (HCWs) are at high risk of HBV infection in the health care settings. The prevalence rate of HBV in HCWs is about 2–10 times higher than the general populations in the world. Methods: A cross sectional study was conducted at GMCH, Udaipur from March 2017 to August 2017 on a pretested, precoded and prestructured self administered questionnaire included sections on knowledge, attitude, and practice toward hepatitis B after having oral/ written consent among 200 medical Students. Results: There were 144 (72.0%) males and 56 (28.0%) females participated as study subjects, more than 80.00% of the study subjects knew about the causative agent, vertical transmission, and vaccine prevention and after effects of HBV infection, 151 (75.50%) agreed for health education for STD’s in the schools, 42 (21.00%) of the study subjects had experienced the needle stuck injury. Conclusions: Although more than 80% students had scientific knowledge about HBV but still there are gaps in the knowledge of Medical Students about Hepatits B infection. Sensitization of the medical students to the various aspects of disease through an active health education programme is crucial to control the spread of Hepatitis B.